2021
DOI: 10.3390/ma14247539
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stability of Screw-Retained Monolithic and Bi-layer Posterior Hybrid Abutment Crowns after Thermomechanical Loading: An In Vitro Study

Abstract: To evaluate the failure-load and survival-rate of screw-retained monolithic and bi-layered crowns bonded to titanium-bases before and after mouth-motion fatigue, 72 titanium-implants (SICvantage-max, SIC-invent-AG) were restored with three groups (n = 24) of screw-retained CAD/CAM implant-supported-single-crowns (ISSC) bonded to titanium-bases: porcelain-fused-to-metal (PFM-control), porcelain-fused-to-zirconia (PFZ-test) and monolithic LDS (LDS-test). Half of the specimens (n = 12/group) were subjected to fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The sample size was determined by the power test focusing on the primary outcome: fracture resistance. The statistical power analysis, based on the study by Spitznagel et al, 16 comparing the fatigue testing fracture resistance of monolithic lithium disilicate to porcelainfused-to-zirconia, revealed that a minimum sample size of n = 9/ group, with a power of 0.97 (effect size d = 1.72), is required for this test, considering an α error probability of 0.05. To ensure an ample sample size, in the present study, the tests were conducted with n = 10/group.…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample size was determined by the power test focusing on the primary outcome: fracture resistance. The statistical power analysis, based on the study by Spitznagel et al, 16 comparing the fatigue testing fracture resistance of monolithic lithium disilicate to porcelainfused-to-zirconia, revealed that a minimum sample size of n = 9/ group, with a power of 0.97 (effect size d = 1.72), is required for this test, considering an α error probability of 0.05. To ensure an ample sample size, in the present study, the tests were conducted with n = 10/group.…”
Section: Experimental Designmentioning
confidence: 99%
“…Despite the methodological variation, previous studies have demonstrated that monolithic zirconia crowns have the lowest chances of chipping, in contrast, bilayered crowns have the highest chance. [14][15][16] Honda et al 14 showed that monolithic screw-retained implant-supported was significantly more fracture-resistant than bilayered crowns. Spitznagel et al 16 showed that porcelain-fused-to-metal, porcelainfused-to-zirconia, and monolithic crown bonded to titanium under thermomechanical cycling, and monolithic crown showed high reliability as an all-ceramic material for screw-retained posterior hybridabutment-crowns.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations